The Use of Documentary Films to Improve Learning Outcomes of Islamic Cultural History in Students - Sukamto (Journal of Education Reseach and Evaluation, 2023)
Documentary film learning media still needs to be used for history lessons in high schools, including the History of Islamic Culture Documentary Films. This study aims to analyze differences in student learning outcomes in the Islamic Cultural History course between groups of students studying explanation documentation and those studying traditional learning. The research approach used is quantitative research. The population of this study amounted to 250 students. It consists of 40 experimental students, and the control class has the same number of 42 students. Data collection method with the test method. Data analysis using quantitative analysis. This study’s results indicate that using a documentary learning environment substantially impacts student learning outcomes in Islamic Cultural History courses. This is supported by the significance value (two-tailed) being less than 0.05, so H0 is approved, and Ha is not. If the significance value (2-tailed) is less than 0.05, then H0 is not approved, and Ha is approved. It can be concluded that the results of student learning in the experimental class and the comparison class, students produced superior grades in the experimental class because they used documentary film media. This research implies that using film learning media makes students more enthusiastic and motivated to participate in learning. Thus, students' learning motivation can be increased by getting to know documentary films.